Etiek en kapitalisme - Labuschagne, J. P. (Hervormde teologiese studies, 1987)
Ethics and capitalism The main purpose of this essay is to demonstrate that, on the basis of Biblical Ethics, criticism on Marxism and Communism does not simultaneously imply adherence to Capitalism, for the most vulnerable point in Classical Capitalism is its lack of ethics as a leading principle. Since the days of Adam Smith, political economy (the common wealth of society) in Capitalism is metaphysically assumed, and in this sense derived, not from reality nor any proven ethical principle, but from a concept of a private economy (the competition of private greed) as a basis for society.